Factors Influencing Financial Freedom in Millennials Based on Gender, Age, Marital Status and Education - Tarigan, Liyandri Rasbina; fitria, apsarini; fauziah, zianah (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of this study was to determine the effect of gender, age, marital status and education on financial freedom in Gen Millenials. The type of research in this study is quantitative. The population is all Millenials born between 1981 - 1996. Sampling in this study used purposive sampling with the criteria of the millennial generation who have property rental businesses such as houses and apartments or the millennial generation who have income from stock investments, bonds or mutual funds. The data collection technique in this study was carried out through an online questionnaire. The data analysis technique used in this study is multiple linear regression analysis, using the Smart PLS Version 4.0. Based on the results of the analysis that has been carried out, it can be concluded that gender affects financial freedom, age does not affect financial freedom, marital status does not affect financial freedom and education affects financial freedom.